A Framework for Monitoring Ecosystems-Based Adaptation to Climate Change: Experience from The Gambia - Gilruth, P.; Duguma, L.A.; Minang, Peter A.; Bah, A.; Jaiteh, M.S.; Mwangi, S.; Ahmad, M. (MDPI, 2021)
Implementing ecosystems-based adaptation (EbA) to climate change is challenged by the need to monitor biophysical, socio-cultural, and economic impacts which are usually context-specific. Therefore, robust frameworks are required that integrate impacts to better understand EbA effectiveness. Monitoring frameworks that are universally applicable to EbA are desirable, however their universal application is problematic as they should reflect a community-driven design that accommodates both donor reporting functions and the generation of local-level data and information to support management actions and community initiatives. Initial products from this research include a generic, five-step process for developing and testing adaptation indicators, a robust framework consisting of (i) the indicators, data and information used to design the framework, (ii) the operational EbA platform that houses and computes the adaptation indicators, and (iii) the participating institutions, and initial, community-level applications to guide water management, replenishment of the vegetation cover, and business development. Immediate benefits to rural communities include the re-orientation of performance indicators mapped to their needs as opposed to donor reporting alone. The framework contributes to the set of tools currently in use for EbA monitoring by offering an umbrella within which existing tools can be applied. Near-term future research will focus on improving the utility of the framework and its platform beyond reporting on key performance indicators (KPIs) by adapting the EbA platform to support changing management needs. Future research will be needed to understand the extent to which the environmental changes in The Gambia compared to changes across the Sahel and Sudano-Sahel regions of West Africa and whether the lessons learned from The Gambia could be extrapolated to the subregion.